Short Communication: Rapid and accurate genetic authentication of Penthorum chinense by improved RAPD-derived species-specific SCAR markers - ZHIQIANG MEI; MD. ASADUZZAMAN KHAN; XIANQIN ZHANG; JUNJIANG FU (Society for Indonesian Biodiversity, 2017)
Mei Z, Khan MA, Zhang X, Fu J. 2017. Short Communication: Rapid and accurate genetic authentication of Penthorum chinense by improved RAPD-derived species-specific SCAR markers. Biodiversitas 18: 1243-1249. For the genetic identification and authentication of living organisms, development of Sequence-Characterized Amplified Region (SCAR) markers from Random Amplified Polymorphic DNA (RAPD) fragments is a valuable molecular approach. By using SCAR markers, molecular analysis is simplified to a Polymerase Chain Reaction (PCR) analysis using PCR primers designed from specific sequences of the RAPD amplicons. In this study, RAPD fragments from improved RAPD amplification of a perennial herb Penthorum chinense Pursh from China were cloned into a T-vector, and positive clones were identified by PCR amplification, and sequenced with the Sanger sequencing method for the SCAR marker development. Five SCAR markers were developed that were very specific to P. chinense, and deposited in GenBank (accession numbers: KX671029, KX671030, KX671031, KX671032 and KX671033). BLAST searches of these five nucleotide sequences in the GenBank database showed no identity with markers from other species. This study was developing five specific SCAR markers, has enabled reliable genetic identification of the herbal plant species Penthorum chinense Pursh, useful for authenticating future samples of this important medicinal herb.